المكان المسرحي رؤیة فلسفیة (Journal of the College of Education for Women, 2019)
The roots of the philosophical concept of place in the old human thoughtextended from his realization to the place he is being in, becomes the exsistingthings that he noticed, form a space in the place. Since here the place is concederedas a container for these bodies.The initial (primitive) human being, through his concept of the placeindicates the sensible phenomena of the concept of the place. Therefore, theconcept of the sensible place, is the prevailing though during that period.Therefore, they distributed the world as (heaven, earth, and the sensible world)where (goods, human beings and the dead).The platonic concept to the idea of time is a circular concept depends on theabsolute religious movement, because it is the movable image. So, the concept ofplace in the ancient human being's thought is prior to their concept of time andmovement, because bodies cannot be found unless in a place determined by it'stemporal moving nature. The Greek philosopher are the initial ones who discussedthe concept of place according to the philosophical view of their age.This research includes four chapters: The first chapter is about themethodical fram which includes the problem of the research, its importance, goaland the definitions of terms. The second chapter includes the theoretical from andthe previous studies. While the third chapter deals with the procedures of theresearch. Chapter four includes the results and the conclusion. The research endswith a list of sources and English abstract.